2021
DOI: 10.1111/luts.12392
|View full text |Cite
|
Sign up to set email alerts
|

Transperineal pelvic floor ultrasound for analyzing the outcomes of pelvic floor surgery for the treatment of anterior compartment prolapse: A comparative study of transvaginal mesh and native‐tissue repair

Abstract: Objective To compare the outcomes of transvaginal mesh (TVM) and native‐tissue repair (NTR) for the repair of anterior compartment prolapse. Methods This retrospective study involved 90 patients with anterior compartment prolapse who underwent pelvic organ prolapse surgery between January 2018 and October 2020. A TVM was used to treat 53 patients and 37 underwent NTR. All patients underwent a standardized interview, clinical examination, and four‐dimensional pelvic floor ultrasound (PFUS) before and after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…Still, they also reported that surgeons should consider different surgical complications, including low back pain and urinary retention in patients. [ 22 ] These data were also in line with the findings of our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Still, they also reported that surgeons should consider different surgical complications, including low back pain and urinary retention in patients. [ 22 ] These data were also in line with the findings of our study.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Liu et al . [ 22 ] reported significantly improved patient symptoms after sacrospinous ligament fixation. Still, they also reported that surgeons should consider different surgical complications, including low back pain and urinary retention in patients.…”
Section: Discussionmentioning
confidence: 99%